2018
DOI: 10.29309/tpmj/2014.21.05.2543
|View full text |Cite
|
Sign up to set email alerts
|

Natural Sexual Offences;

Abstract: Introduction: Globally, rape of women is a serious health, social and religiousconcern and is considered as a violation of women basic human right. Objective: The aim wasto ascertain incidence of natural sexual offence (rape) in Punjab and to analyze the data withrespect to sociodemographic characteristics, findings of medicolegal examination and resultsof evidence collected from victims of sexual assault. Material and Method: This retrospectivestudy was conducted on 148 female victims of rape brought to Foren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
3
3
2
Order By: Relevance
“…The results of our study were in contrast to the results of Arif et al 22 who reported that 122 (82.4%) survivors had changed clothes, 26 (17.57%) had changed clothes but did not wash and handed over the clothes worn at the time of assault. In the present study, dried secretions were found on clothing, bed sheets and bag of survivor in 34 (23.94%) cases.…”
Section: Status Of Survivor and Spermatozoa On Clothescontrasting
confidence: 99%
See 2 more Smart Citations
“…The results of our study were in contrast to the results of Arif et al 22 who reported that 122 (82.4%) survivors had changed clothes, 26 (17.57%) had changed clothes but did not wash and handed over the clothes worn at the time of assault. In the present study, dried secretions were found on clothing, bed sheets and bag of survivor in 34 (23.94%) cases.…”
Section: Status Of Survivor and Spermatozoa On Clothescontrasting
confidence: 99%
“…33 2 (1.41%) survivors were pregnant and assailants were found to be biological father of the offspring. The results were in line with the study of Arif et al 22 who reported pregnancy in 2 (1.3%) cases after the assault. The results of our study were close to the results of Pal et al 24 who mentioned that 1 (2.85%) survivor was pregnant after the sexual assault.…”
Section: Link Between Menstruation Semen and Spermatozoasupporting
confidence: 92%
See 1 more Smart Citation
“…Majority of the victims (77.6%) showed old hymen tears. Spermatozoa were found in 18.2% of the cases (11). 43% of the victims were 12 to 16 years of age followed by 16 to 20 years 21%.…”
Section: Discussionmentioning
confidence: 93%
“…In the case of a stranger perpetrator, the rape is termed stranger rape. It is of three types; contact sexual assault, blitz sexual assault, and home invasion sexual assault [3].…”
Section: Introductionmentioning
confidence: 99%